Triterpenoid Saponins From the Fruit of Acanthopanax senticosus (Rupr. & Maxim.) Harms - Liu, Yan; Jiang, Peng; Zhang, Mei-Ling; Pan, Juan; Guan, Wei; Li, Xiao-Mao; Yang, Bing-You; Kuang, Hai-Xue (Frontiers in Chemistry, 2022)
Five new oleanane-type triterpenoid saponins (1–5), together with 24 known saponins (6–29) were isolated from the fruit of Acanthopanax senticosus. Their structures were determined by extensive spectroscopic analysis, including 1D, 2D nuclear magnetic resonance (NMR), and high-resolution electrospray ionization mass spectrometry (HR-ESI-MS), in combination with chemical methods (acid hydrolysis). The neuroinflammation model was established by lipopolysaccharide (LPS)-induced BV2 microglia, and the neuroprotective effects of all compounds (1–29) were evaluated.